Freedom, Volition, Ego Development, Personal Responsibility, and Internal Chattering within Us - Casiglia, Edoardo; Gadotti, Erik (Advances in Social Sciences Research Journal, 2026)
This paper advances a paleo-psychological reconstruction of the evolution of human consciousness, arguing that the Ego is a relatively recent development in Homo sapiens. For most of human history, individuals are proposed to have functioned without reflective consciousness, initially guided by instinct and later by a symbolic, non-verbal Unconscious. Around 60,000 years ago, a primitive symbolic thought emerged, marking the development of the Unconscious. The later emergence of articulated language (approximately 35,000 years ago) profoundly transformed mental structure, rendering the Unconscious increasingly verbal. This shift gave rise to the bicameral mind, characterized by internally-generated cortical voices experienced as external, authoritative commands – often attributed to leaders or deities – and not subject to critical evaluation due to the absence of a conscious Ego. The transition to Ego consciousness is situated around the second millennium BC and is linked to cultural and environmental factors, including the rise of writing and abstraction, as well as disruptive historical events. The disappearance of bicameral voices is hypothesized to have selected individuals capable of generating a meta-representational function: the Ego, a complex emerging from the Unconscious and endowed with self-awareness. Despite this transition, remnants of bicameral voices persist in modern humans as unconscious processes influencing behaviour, decision-making, and moral frameworks. These processes manifest in both pathological conditions (e.g., schizophrenia, obsessive-compulsive disorder, Tourette syndrome, etc.) and normal cognition (e.g., inner speech, cultural conditioning, moral principles, and preconscious neural activity preceding decisions). Consequently, conscious will is interpreted as illusory, grounded in underlying unconscious mechanisms shaped by evolutionary history.